Managing the Miombo Woodlands of Southern Africa : Policies, Incentives, and Options for the Rural Poor - Dewees, Peter A.; Campbell, Bruce M.; Katerere, Yemi; Sitoe, Almeida; Cunningham, Anthony B.; Angelsen, Arild; Wunder, Sven (World Bank, Washington, DC, 2014)
This report is based on seven background papers comprising household studies, national level analyses, and technical assessments. Household studies were undertaken in Mozambique and Zambia to develop a clearer picture of the role of Miombo woodlands in household consumption. These studies were an outcome of intensive, seasonal structured household surveys, which have formed the core of the original work supported by this project (technical annexes one, two, and three). Two national level assessments were carried out, the first in Zambia on the contribution of dry forests to economic development. This assessment was derived from a synthesis of empirical household studies, policy research, silvicultural and ecological studies, and other primary sources (technical annex four). The second country case study reviewed community-based woodland management opportunities in Mozambique and synthesized the results of other primary studies (technical annex five). The author also reviewed what is known about miombo silviculture and how management systems could be improved or otherwise put in place to increase productivity (technical annex six). Technical annex seven focuses on policy options for improving management. There are obvious geographic gaps in coverage in this paper. Angola and Democratic Republic of Congo (DRC) were not covered to any significant extent. This is partly because the available body of miombo research largely excludes these miombo-rich countries. It was also not our intention to provide a comprehensive country-by country overview of the status of miombo woodlands and the policies, institutions, and legislation that are affecting their use. This shortcoming notwithstanding, our efforts focused on teasing out some of the complexities of miombo use and management in the individual technical annexes.